A move towards just sustainability: transformation of discourses around urban sustainability planning in Seoul, Republic of Korea. Issue 3 (4th March 2023) - Jung, Yoonhee
ABSTRACT: This paper examines the discourses of urban politics around the decision-making processes and the implementation of two sustainability projects in Seoul – the Cheonggyecheon Restoration Project and the Remaking Sewoon Project. Using an archival analysis, it investigates how the recent rapid socio-economic transformations in Korea have affected the discourses around the urban politics of sustainable policies in Seoul. "Green" has become a new paradigm for urban redevelopment in Korea since the early 2000s, and the research finds that the Seoul Metropolitan Government (SMG) uses sustainability plans as a "sustainability fix" heavily focused on "pro-growth" development to win support for its restoration projects among citizens and for global approval. However, with increased democratization and the growing role of civic groups in urban politics, we see a move towards more just sustainability in urban sustainability planning in Korea.